Alternativ-Entwurf | Audiovisuelle Dokumentation der Hauptverhandlung (AE-ADH) - Arbeitskreis deutscher, österreichischer und schweizerischer Strafrechtslehrer (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
German criminal procedure does not provide for verbatim records of criminal trials. This is quite different from most other European countries where at least audio recordings exist. However, technological progress has fueled a lively political debate in recent years. The "Arbeitskreis Alternativ-Entwurf" contributes to this debate by presenting a comprehensive draft bill which provides for a complete change of technology. The current written record of the bare formalities will be replaced by the video-recording of the entire trial. The intent is to enhance the truth-finding process of the trial court and to provide the appeals courts with a better, more reliable documentation to correct procedural and grave fact-finding errors. With contributions by Prof. Dr. Felix Bommer; Prof. Dr. Dr. h.c. mult. Albin Eser; Prof. Dr. Helmut Frister; Prof. Dr. Matthias Jahn; Prof. Dr. Dr. h.c. Heike Jung; Prof. Dr. Michael Lindemann; Prof. Dr. Bernd-Dieter Meier; Prof. Dr. Carsten Momsen; Prof. Dr. Rudolf Rengier; Prof. Dr. Kurt Schmoller; Prof. Dr. Carl-Friedrich Stuckenberg, LL.M. (Harvard); Prof. Dr. Torsten Verrel; Prof. Dr. Thomas Weigend and Prof. Dr. Wolfgang Wohlers.